2020
DOI: 10.1039/c9me00149b
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring and packing of self-assembled monolayers ofsemithio-bambusurils on Au(111)

Abstract: Self-assembled monolayers have been formed of semithio-bambusurils that undergo conformational changes to direct all S atoms to the gold surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…We also determined the fraction of sulfur anchoring groups that participated in binding to the metal surface for each analyzed SAM by summing the integrals of both bound and unbound S 2p bands. For example, in the XPS spectra of 4 a , the calculated value obtained for the bound sulfur was 61 % (Table 2), implying that sulfur atoms at both rims are involved in binding to the Au surface and suggesting less dense layers with potentially complete loss of anion binding affinity [34] . In contrast, a smaller fraction of bound S−Au was observed in the XPS spectra of SAMs of 4 c (36 %), inferring that only one rim is involved in the assembly process onto the gold surface.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We also determined the fraction of sulfur anchoring groups that participated in binding to the metal surface for each analyzed SAM by summing the integrals of both bound and unbound S 2p bands. For example, in the XPS spectra of 4 a , the calculated value obtained for the bound sulfur was 61 % (Table 2), implying that sulfur atoms at both rims are involved in binding to the Au surface and suggesting less dense layers with potentially complete loss of anion binding affinity [34] . In contrast, a smaller fraction of bound S−Au was observed in the XPS spectra of SAMs of 4 c (36 %), inferring that only one rim is involved in the assembly process onto the gold surface.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in the XPS spectra of 4 a, the calculated value obtained for the bound sulfur was 61 % (Table 2), implying that sulfur atoms at both rims are involved in binding to the Au surface and suggesting less dense layers with potentially complete loss of anion binding affinity. [34] In contrast, a smaller fraction of bound SÀ Au was observed in the XPS spectra of SAMs of 4 c (36 %), inferring that only one rim is involved in the assembly process onto the gold surface. The attenuation of the bound sulfur signal caused by the location of these atoms at the bottom of the SAM may explain the < 50 % value observed here.…”
Section: Xps Studiesmentioning
confidence: 95%
See 2 more Smart Citations
“…These macrocycles are rigid molecules due to the high steric demands of their subunits, which are locked in an alternate arrangement. Moreover, we demonstrated that sulfur analogues of BU[4], which are too small to accommodate any type of guest, have shown much potential for the formation of metal–organic chain polymers , and in anchoring self-assembled monolayers (SAMs) on gold surfaces . Therefore, designing inherently chiral hetero -BUs would be appealing for developing applications in the field of chiral sensing technologies.…”
Section: Introductionmentioning
confidence: 99%